2000
DOI: 10.1177/088572880002300203
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Employment Earnings: Extended Transition Services that Make a Difference

Abstract: A pre-test-post-test control group design examined the effects of extending transition services beyond graduation on employment earnings of vocational students with disabilities. Specific transition services included: vocational assessment, agency contacts, Individualized Educational Program (IEP) meetings, extended vocational training, employability counseling, job club, job interview preparation, job development, and job coaching. The results indicated that youth who received extended transition services had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Although a functional relationship does imply a "robust" independent variable (Baer, 1977), it does not quantify the effect size as the Percentage of Non-Overlapping Data (PND; Scruggs & Mastropieri, However, because the group design quality indicators checklist did not include an assessment of intervention "effects," we did attempt to calculate effect sizes for the six group studies used in our review (i.e., Bates, Cuvo, Miner, & Korabek, 2001;Izzo, Cartledge, Miller, Growick, & Rutkowski, 2000;Martin et al, 2006;Nelson, Smith, & Dodd, 1994;Sinclair, Christensen, and Thurlow (2005); Van Reusen & Bos, 1994). Using Cohen's d, effect sizes were d = 0.334 (Self -Advocacy Strategy; Van Reusen & Bos, 1994), d = 0.588 (extending services beyond secondary school; Izzo et al, 2000), and d = 1.53 (teaching job applications; Nelson et al, 1994). Effect sizes for the other three studies were not, or could not be, calculated.…”
Section: Limitationsmentioning
confidence: 99%
“…Although a functional relationship does imply a "robust" independent variable (Baer, 1977), it does not quantify the effect size as the Percentage of Non-Overlapping Data (PND; Scruggs & Mastropieri, However, because the group design quality indicators checklist did not include an assessment of intervention "effects," we did attempt to calculate effect sizes for the six group studies used in our review (i.e., Bates, Cuvo, Miner, & Korabek, 2001;Izzo, Cartledge, Miller, Growick, & Rutkowski, 2000;Martin et al, 2006;Nelson, Smith, & Dodd, 1994;Sinclair, Christensen, and Thurlow (2005); Van Reusen & Bos, 1994). Using Cohen's d, effect sizes were d = 0.334 (Self -Advocacy Strategy; Van Reusen & Bos, 1994), d = 0.588 (extending services beyond secondary school; Izzo et al, 2000), and d = 1.53 (teaching job applications; Nelson et al, 1994). Effect sizes for the other three studies were not, or could not be, calculated.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, Great Oaks program participants were more likely to be involved in social groups, and have saving accounts and credit cards (Izzo & Lamb, 2003). Finally, young women who participated in this study were more likely to obtain employment than their peers nationally (Izzo et al, 2000).…”
Section: Career Interventions For Youth With Disabilitiesmentioning
confidence: 88%
“…Students with disabilities who are enrolled in this program receive tutoring services, and learn communication, goal setting, and time management skills. Moreover, students with disabilities work with job coaches during their community-based vocational training experiences (Izzo, Cartledge, Miller, Growick, & Rutkowski, 2000).…”
Section: Career Interventions For Youth With Disabilitiesmentioning
confidence: 99%
“…Further, Wehman (2001) reported that community-based experiences appeared to decrease the likelihood of students dropping out of high school. Finally, enrollment in additional transition services, such as CBT programs, beyond graduation has been found to lead to significantly higher earnings and higher rates of participation in postsecondary training programs (Izzo, Cartledge, Miller, Growick, & Rutkowski, 2000). In short, the results of these studies suggest that the components of CBT programs may positively impact adult life outcomes such as employment and postsecondary education.…”
mentioning
confidence: 88%